Analisis Pengaruh Kualitas Pelayanan dan Kepercayaan terhadap Loyalitas Pelanggan Shopee - Yusuf Maulana Rextianto; Zahra (Jurnal Semesta Ilmu Manajemen dan Ekonomi, 2025)
The rapid development of e-commerce has transformed consumer shopping behavior, with Shopee emerging as one of Indonesia’s leading online marketplaces. In an increasingly competitive market, customer loyalty is influenced by service quality and trust. This study aims to analyze the impact of these two factors on Shopee customer loyalty. Using a quantitative approach, data were collected through a survey of 60 active Shopee users and analyzed using multiple linear regression. The results indicate that both service quality and trust significantly affect customer loyalty, with a combined explanatory power of 61.6%. Individually, service quality accounts for 47.7% of customer loyalty variation, while trust explains 56.1%. These findings highlight the importance of improving service efficiency and transaction security to enhance customer retention. Practically, Shopee should optimize its customer service, ensure transparent policies, and strengthen user trust to maintain a competitive edge. This study provides valuable insights for e-commerce businesses in developing strategies to foster long-term customer loyalty.